VIOLENCE AS A PRECURSOR OF POST-TRAUMATIC STRESS DISORDER AND THE IMPACT ON WOMEN'S HEALTH (CIPEEX, 2022)
IT IS NOTABLE THAT FROM INFANCY TO THE END OF LIFE, WOMEN ARE SUSCEPTIBLE TO RAPE IN VARIOUS SPHERES, SINCE VIOLENCE EXTENDS FROM SEXUAL, PHYSICAL, PSYCHOLOGICAL AND EVEN OBSTETRIC. THIS REALITY REFLECTS IN BIOPSYCHOSOCIAL CONDITIONS SUCH AS DEPRESSION, ANXIETY, SELF-BLAME, SOCIAL ISOLATION AND, IN PARTICULAR, IS A PREVALENT FACTOR IN THE DEVELOPMENT OF POSTTRAUMATIC STRESS DISORDER. OBJECTIVE OF THE STUDY IN VOGUE SEEKS TO CARRY OUT AN INTEGRATIVE REVIEW OF THE LITERATURE ANALYZING HOW VIOLENCE ACTS AS A PRECURSOR OF POST-TRAUMATIC STRESS AND ITS IMPACT ON WOMEN'S HEALTH. TO THAT END, 21 PAPERS PUBLISHED BETWEEN 2014 AND 2018 WERE SELECTED, BEING 18 IN ENGLISH AND 3 IN PORTUGUESE USING THE DECS: POST-TRAUMATIC; "VIOLENCE AGAINST WOMEN"; "POST-TRAUMATIC STRESS" AND "VIOLENCE". RESCUING ARTICLES FROM THE LATIN AMERICAN AND CARIBBEAN LITERATURE IN HEALTH SCIENCES (LILACS), MEDICAL LITERATURE ANALYSIS AND RETRIEVAL SYSTEM ONLINE (MEDLINE), SCIENTIFIC ELECTRONIC LIBRARY ONLINE (SCIELO) AND PUBLIC MEDLINE (PUBMED) PLATFORMS. IN THIS WAY, IT WAS POSSIBLE TO RATIFY THE INTIMATE RELATIONSHIP BETWEEN VIOLENCE AGAINST WOMEN AND THE DEVELOPMENT OF PTSD, IN ADDITION TO IDENTIFYING AGGRAVATING FACTORS SUCH AS CHILDHOOD TRAUMAS, INTIMATE PARTNER VIOLENCE (IPV), REVICTIMIZATION, INTERCURRENCES DURING MOTHERHOOD, HUMAN IMMUNODEFICIENCY (HIV), LOW SELF-ESTEEM, COGNITIVE DEFICIT, SHELTER AND INSUFFICIENT SOCIAL ASSISTANCE. THEREFORE, IT IS NECESSARY TO PAY MORE ATTENTION TO THE CONDITIONS PREDISPOSING TO THE TRAUMATIC EVENT AND THE CHRONIFICATION OF THE DISORDER.
Keywords: Posttraumatic Stress Disorder (PTSD). Violence. Woman. Trauma.